2004
DOI: 10.1021/ja044733l
|View full text |Cite
|
Sign up to set email alerts
|

The Total Synthesis of (−)-SNF4435 C and (+)-SNF4435 D

Abstract: The size and positioning of substituents on a tetraene, along with the Woodward-Hoffmann rules, control the relative stereochemistry at the four adjacent chiral centers that are generated in the 8pi/6pi electrocyclization cascade. A biomimetic synthesis of (-)-SNF4435 C and (+)-SNF4435 D exploits these steric effects and allows confirmation of the predicted absolute stereochemistry of the natural products.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
29
0
6

Year Published

2005
2005
2013
2013

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 86 publications
(41 citation statements)
references
References 23 publications
6
29
0
6
Order By: Relevance
“…[93] Ein Bei- Aufsätze gruppen um Sasaki [99] und Yamamoto [100] [105] entwickelten Totalsynthesen von SNF4435 C (118) und SNF4435 D (119, Schema 23), zwei immunsuppressiven Wirkstoffen aus der Kulturbrühe von Streptomyces spectabilis. [106] Die zentrale Bicyclo[4.2.0]octadien-Struktur dieser faszinierenden Naturstoffe erinnert stark an die Endiandrinsäu-ren, [107] für die Black und Mitarbeiter einen Biosynthesepfad mit einer Elektrocyclisierungskaskade vorschlugen, [108] der anschließend -vor nun über 20 Jahren -experimentell durch unsere Arbeitsgruppe bestätigt wurde.…”
Section: Stille-reaktionenunclassified
“…[93] Ein Bei- Aufsätze gruppen um Sasaki [99] und Yamamoto [100] [105] entwickelten Totalsynthesen von SNF4435 C (118) und SNF4435 D (119, Schema 23), zwei immunsuppressiven Wirkstoffen aus der Kulturbrühe von Streptomyces spectabilis. [106] Die zentrale Bicyclo[4.2.0]octadien-Struktur dieser faszinierenden Naturstoffe erinnert stark an die Endiandrinsäu-ren, [107] für die Black und Mitarbeiter einen Biosynthesepfad mit einer Elektrocyclisierungskaskade vorschlugen, [108] der anschließend -vor nun über 20 Jahren -experimentell durch unsere Arbeitsgruppe bestätigt wurde.…”
Section: Stille-reaktionenunclassified
“…183,184,187 The effects of substituents on the diastereoiomeric ratios observed in tetraene-cyclooctatriene-bicyclooctadiene cyclizations are not easily rationalized. 182 Parker and Wang 188 investigated diastereoselectivity in an auxiliary-controlled 8p electrocyclization through an 8p-6p cascade (in which the 6p component was known to cyclize in a stereoselective manner). 183,184,187 A series of chiral auxiliarybearing tetraenic esters were assembled using a Stille coupling and their in situ electrocyclization to form the core ring system of (À)-SNF4435 C and (+)-SNF4435 D was investigated (Scheme 35).…”
Section: Thermal Reactions 4p Electrocyclizations ( P 4 a )mentioning
confidence: 99%
“…Parker et al reported the first total synthesis, having used a very similar coupling strategy as Trauner to access the (−E,2Z,4Z,6Z)-tetraene 95 (Scheme 16.22a) [62]. The vinyl iodide 98 and the vinyl stannane 103 underwent Pd-catalyzed cross coupling to give the tetraene 95, which then underwent the expected electrocyclization cascade to 90/91.…”
Section: Endiandric Acidsmentioning
confidence: 99%